2014
DOI: 10.1002/2014ja019943
|View full text |Cite
|
Sign up to set email alerts
|

Formation processes of flux ropes downstream from Martian crustal magnetic fields inferred from Grad‐Shafranov reconstruction

Abstract: We applied the Grad-Shafranov reconstruction (GSR) technique to Martian magnetic flux ropes observed downstream from strong crustal magnetic fields in the southern hemisphere. The GSR technique can provide a two-dimensional axial magnetic field map as well as the axial orientation of flux ropes from single-spacecraft data under assumptions that the structure is magnetohydrostatic and time independent. The reconstructed structures, including their orientation, allowed us to evaluate possible formation processes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
34
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 52 publications
7
34
0
Order By: Relevance
“…The inferred flux rope axis was approximately oriented along the + Z mso direction, indicating that it was created via multiple X line reconnection between the local crustal and overlaid interplanetary magnetic fields draped around Mars (Figure ). This formation process was previously proposed by Hara et al []. Hence, these MAVEN observations can convincingly show that this formation process surely operated under the Martian plasma environment. Figure suggested that the giant ionospheric flux rope was detected when an ICME impacted Mars.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The inferred flux rope axis was approximately oriented along the + Z mso direction, indicating that it was created via multiple X line reconnection between the local crustal and overlaid interplanetary magnetic fields draped around Mars (Figure ). This formation process was previously proposed by Hara et al []. Hence, these MAVEN observations can convincingly show that this formation process surely operated under the Martian plasma environment. Figure suggested that the giant ionospheric flux rope was detected when an ICME impacted Mars.…”
Section: Discussionsupporting
confidence: 85%
“…The estimated chirality (handedness) of the flux rope magnetic fields is also consistent with the recovered two‐dimensional structure in Figure c. Although Hara et al [] also pointed out a possibility of this proposed formation process, our results show stronger evidence for this proposed formation process to operate under the Martian ionosphere.…”
Section: Possible Formation Processsupporting
confidence: 90%
See 1 more Smart Citation
“…Hara et al [, ] previously investigated the magnetic flux ropes observed by MGS around Mars to understand the possible ion escape rates associated with flux ropes, although MGS lacked the ion measurements. Recently, Hara et al [] recovered the spatial structure of a detached magnetic flux rope based on the MAVEN simultaneous plasma and magnetic field measurements.…”
Section: Estimation Of Flux Ropes' Spatial Properties Reconstructed Vmentioning
confidence: 99%
“…Alternatively, we can explore the second possibility that does not necessitate magnetotail reconnection: transport of flux ropes that are originally generated in the dayside ionosphere through plasma instabilities such as helical kink, Kelvin‐Helmholtz instabilities [e.g., Elphic and Russell , ; Wolff et al , ; Ruhunusiri et al , ], and magnetic reconnection in consequence of interactions between the IMF and crustal fields [e.g., Hara et al , , ], or dayside magnetic reconnection analogous to the terrestrial flux transfer events [see, e.g., Hasegawa , , and references therein]. As illustrated in Figure b, these helical draped magnetic field lines can be subsequently transported into the nightside magnetotail forming the current sheet, allowing spacecraft to detect them as flux ropes embedded in the magnetotail current sheets.…”
Section: Introductionmentioning
confidence: 99%